Accumulation of Nucleolar Inorganic Polyphosphate Is a Cellular Response to Cisplatin-Induced Apoptosis - Xie, Lihan; Rajpurkar, Asavari; Quarles, Ellen; Taube, Nicole; Rai, Akash S.; Erba, Jake; Sliwinski, Benjamin; Markowitz, Moses; Jakob, Ursula; Knoefler, Daniela (Frontiers in Oncology, 2019)
The chemotherapeutic drug cisplatin, which targets DNA, serves as one of the main staples in cancer treatment. Yet the therapeutic application of cisplatin is limited by two major challenges: the occurrence of reversible and irreversible side effects due to non-specific toxicity, and the intrinsic or developing resistance of tumor cells towards cisplatin. Here we demonstrate that cancer cells respond to cisplatin treatment with the nucleolar accumulation of inorganic polyphosphate (polyP), a universally conserved high-energy compound. PolyP accumulation positively correlates with the levels of activated caspase-3, suggesting a novel role of polyP in cisplatin-mediated apoptosis. In support of this finding, we discovered that administration of exogenous polyP increases cisplatin-induced toxicity in select cancer cell lines, raising the exciting possibility that enhancing endogenous polyP levels might be a novel mechanism to sensitize cancer cells to cisplatin treatment.